Fifty Years of Forestry in Indepenqent India - Gains and Losses - Chaturvedi, A. N. (Indian Forester, 1998)
This article reflects on the past, present and future scenario of forest management in India. The status of major forests, Social Forestry, Joint Forest Management, Forestry Research, Forest Education, Forest Based Industries have also been discussed.